Surveillance of surgical site infection. Issue 2 (12th March 2012) - Nicchia, A.; Paradiso, F.; Russo, C.; Saturnino, P.; Serio, C.
Abstract : Background: Nosocomial infections are one of the most relevant cause of morbidity and mortality; also, they markedly contribute to increment the cost of healthcare. The most frequent are the infections following surgery or invasive medical procedures for example cross-contamination. Monitoring and prevention of the sources that are involved in the development of the nosocomial infection is performed at the Antonio Cardarelli Hospital of Naples which provides the corresponding corrections. Purpose: Aim of the project Surveillance of surgical site infection is the promotion of the prophylaxis guidelines and the control of the Healthcare-Associated Infections. Materials and methods: Within this project the role of the Pharmacy is to enable the targeting of the patients using specific antibiotic-based therapies. The project foresees the recording and the screening of the clinical folders of all the patients which underwent to surgery between the year 2010/2011 in Operative Units of Cancer surgery, Gastroenterology surgery, Gynaecology, Emergency Neurosurgery and Orthopaedics and Knee Surgery. All the antibiotic therapies followed by the patients either for the prophylaxis or for the treatment of possible postsurgical infections, are registered in specific schedules. Subsequently, the collected data, especially the one related to the prophylaxis, are compared with the standard corporate protocols and inserted in the regional documents. Results: The choice of the antibiotic prophylaxis is mostly not comparable with the corporate protocols, usually because antibiotics used for the treatment of serious infections are favoured to the detriment of the one applied for surgical prophylaxis. Moreover, the administration times should be reviewed because often they are longer than those provided by the guidelines. Conclusions: Once the critical issues have been emphasised and the specific corrections applied, a reduction in infections should be achieved, resulting in benefits not only in term of therapies optimisation but also in the reduction of the healthcare costs.